Heat transfer rate of swirling impinging jets issuing from a twisted tetra-lobed nozzle - Wongcharee, Khwanchit; Kunnarak, Kengkla; Chuwattanakul, Varesa; Eiamsa-Ard, Smith (My University, 2020)
Heat transfer augmentation by swirling impinging jets delivered through twisted tetra-lobed nozzles (T-LT) is reported. Impinging jets delivered through a circular nozzle (CT: non-swirling jet) and a tetra-lobed nozzle (LT: non-swirling jet) were also tested for comparison. Experimental results showed that Nusselt numbers of impinging jets delivered through all nozzles were increased with Re and decreasing L/Dh. At a given jet Reynolds number (Re) and a jet-to-plate spacing (L/Dh), the impinging jets delivered through the twisted tetra-lobed nozzles and tetra-lobed nozzle yielded superior heat transfer to that delivered by a circular nozzle. For the jets delivered through the twisted tetra-lobed nozzles, the stagnation Nusselt number (Nu) was decreased while the radial heat transfer distribution was improved with decreasing twist ratios of the nozzle. For the investigated range, the jet delivered through the twisted tetra-lobed nozzle with twist ratio of 4.0 yielded a maximal average Nusselt number. Furthermore, the twisted tetra-lobed nozzles (T-LT) with twist ratios of y/Dh = 2.0, 3.0, 4.0 and 5.0 generate higher heat transfer rates than those of the circular nozzle (CT: non-swirling jet) by around 27.7%, 25.0%, 21.6% and 19.3%, respectively.
Keywords: Heat transfer rate; Impinging jet; Swirling impinging jet; Tetra-lobed nozzle; Twisted tetra-lobed nozzle